New Japanese Survey Vessel "Takuyo" - Nakanishi, Akira (The International Hydrographic Review, 2015)
The Hydrographic Department, Maritime Safety Agency, Japan, has commissioned a new survey vessel named Takuyo. She was commissioned on 31 August 1983 and has been designed to carry out hydrographic and geological surveys and oceanographic observations by using her modern survey/observation equipment such as an integrated navigation system, a Seabeam precision bathymetric system, and a digital marine seismic profiling system, as well as to perform long-range cruises covering the waters in the north-western Pacific Ocean.